Association Of Age And Gender Of Patients Who Underwent Amalgam Restoration In Maxillary Second Premolar With Class 1 Dental Caries - ANJUM, A. SHAMAA; ANTONY S, DELPHINE PRISCILLA (The journal of contemporary issues in business and government, 2021)
Dental restoration restores the parts of the tooth structure and missing teeth. An economic, stable and aesthetic restorative material for posterior teeth as an alternative to silver amalgam has long eluded the dental profession. It has been used for more than 150 years and constitutes approximately 75% of all restorative materials used by dentists. Both composite and amalgam are considered to be suitable direct filling materials for restoring class 1 and 2 cavities. Nowadays, the use of amalgam is reducing and gradually composite resin is expected to replace it in near future. The purpose of the study was to evaluate the association of age and gender of patients who underwent amalgam restoration in maxillary second premolar with class 1 cavity. This is a descriptive study which was performed under a university setting in the year 2020. The data of patients who underwent amalgam restoration in the second maxillary premolars from June 2019 to March 2020 was collected by reviewing patients records and analysing data of 86000 patients. The collected data was compiled , reviewed, tabulated and entered in SPSS software for statistical analysis. The study showed a female predilection (64%) and class 1 amalgam restoration in maxillary second premolar were common in patients of 34 years of age. There is no significance of age and gender. Within the limits of the study , it is evident that class 1 amalgam restorations in the maxillary second premolars were more common among the patients of 34 years of age and prevalent among the females. The study also showed that males of 41 years of age and females of 34 years of age were commonly found to have class 1 amalgam restoration in maxillary second premolars. Chi square test was done and Pearson chi square value was found to be p=0.462; hence statistically not significant (p>0.05).